Simple Risk Stratification based on Killip Classification and the Six-minute Walk Test Borg Scale for Outcomes of Acute Coronary Syndrome for Papuanese People in Rural Hospital - Ahmad Zaid Alhamid; Herlina Yulidia; Intan Iriani Supriatna (Universitas Airlangga, 2021)
Background: Accurate risk stratification for untoward outcomes after acute coronary syndrome patients may help clinicians guide the type and intensity of therapy. Unfortunately, most of the Papuanese people face difficulties in accessing sophisticated medical treatment. Aims: The aim of this study was to determine the simplest but most accurate risk stratification for ACS patients treated in rural hospital. Methods: This was a cross-sectional study conducted in Sele Be Solu Regional Hospital at Sorong Regency in West Papua Province. Fifteen unselected patients from September 2019 to March 2020 period with ACS were prospectively studied. All the data were collected from medical records. Results: Subject characteristics mostly were male (80%) and mean age was 54 years, (13,3%) subjects were age less than 45 years. The most diagnosed ACS type was STEMI (73,3%). Conclusion:In Papuanese patients with ACS in rural hospital, those at highest risk can be identified using Killip classification and The Six-minute Walk Test Borg Scale as short term predictor for ACS patients’ outcome.